Determination of the optimal programmed intermittent epidural bolus volume of bupivacaine 0.0625% with fentanyl 2 μg.ml−1 at a fixed interval of forty minutes: a biased coin up‐and‐down sequential allocation trial1. (2nd December 2017) - Zakus, P.; Arzola, C.; Bittencourt, R.; Downey, K.; Ye, X. Y.; Carvalho, J. C.
Summary: The optimum time interval for 10 ml boluses of bupivacaine 0.0625% + fentanyl 2 μg.ml −1 as part of a programmed intermittent epidural bolus regimen has been found to be 40 min. This regimen was shown to be effective without the use of supplementary patient‐controlled epidural analgesia boluses in 90% of women during the first stage of labour, although with a rate of sensory block to ice above T6 in 34% of women. We aimed to determine the optimum programmed intermittent epidural bolus volume at a 40 min interval to provide effective analgesia in 90% of women (EV90 ) during the first stage of labour, without the use of patient‐controlled epidural analgesia. We performed a prospective double‐blind dose‐finding study using the biased coin up‐and‐down sequential allocation method in 40 women. The estimated EV90 was 11.0 (95%CI 10.0–11.7) ml with the isotonic regression method and 10.7 (95%CI 10.3–11.0) ml with the truncated Dixon and Mood method. Overall, 18 women had a sensory block above T6, and 37 women exhibited no motor block. No women required treatment for hypotension. In conclusion, it is not possible to reduce the programmed intermittent epidural bolus volume from 10 ml, used in our current regimen, without compromising the quality of analgesia. Using this regimen, a high proportion of women will develop a sensory block above T6.